Letter from Zach Read to James Curtis Booth, November 17, 1859 - Read, Zach (1859)
James Curtis Booth (1810-1888) is elected a corresponding member of the Burlington County Lyceum of History and Natural Science.
Keywords: Booth, James Curtis, 1810-1888; Lyceums; Natural history--Societies, etc.; Societies